The Fracture Toughness of Fe2B Formed on Boronized AISI 304 - Topuz, Polat; Gundogdu, Emine; Yilmaz, Eren; Gumus, Emre (CARL HANSER VERLAG, 2014)
In this study, the fracture toughness of Fe2B boride layer on boronized AISI 304 stainless steel was investigated. Samples were boronized in an indirect heated fluidized bed furnace with Ekabor 1 (TM) boronizing agent at 1123 K, 1223 K, and 1323 K for 1 h, 2 h, and 4 h, respectively. The boride phases were investigated by X-ray diffraction (XRD) analysis. Hardness and fracture toughness of borides were measured via Vickers indentation. With increasing boriding temperature and time the fracture toughness values were reduced. The boride layer thickness formed on the boronized samples ranged between 12 mu m and 176 mu m. The hardness of the borides ranged between 1709 HV0.1 and 2119 HV0.1 and fracture toughness was in the range of 2.19-4.47 MPa x m(1/2) depending on the layer thickness and hardness.
Keywords: Materials testing; boronizing; AISI 304 steel; hardness; fracture toughness; STEEL; Materials Science